Evaluation of Rice Genotypes for Resistance to Brown Planthopper (Nilaparvata lugens Stål) Populations from the Central Region of Thailand - Sreewongchai, Tanee; Worede, Fisseha; Phumichai, Chalermpol; Sripichitt, Prapa (Agriculture and Natural Resources, 2015)
Intensive cultivation of rice is believed to be one of the factors responsible for the outbreak of brown planthopper (BPH). An experiment was conducted to study the reaction of 22 rice genotypes to six populations of BPH collected from rice research centers and from farmers’ fields of central Thailand. The results showed that populations of BPH from rice research centers were relatively more virulent than those from farmers’ fields. Cluster analysis using the mean BPH damage score divided the genotypes into three groups. Group I contained 18 susceptible genotypes including the susceptible check TN1. Group II contained two moderately resistant genotypes, IR64 and RD31, while the third group was made up of the resistant checks, Rathu Heenati and Ptb33. Rathu Heenati and Ptb33 could be used as sources of resistance for BPH in central Thailand. However, it is important to study the reaction of more genotypes by using additional BPH populations. The differential response of genotypes to populations of rice research centers and farmers’ fields of the same province also needs further investigation.